Everyday racism, museums, and museology: unarchiving black memories through undisciplined writing (Cadernos de Sociomuseologia, 2025)
This text, written as a “political act,” discusses how everyday racism is intertwined with museum discourse and validates the “fabricated narratives of enslavement in museums” when they stage the symbolic subordination of black female bodies through their long-term exhibitions, even in the 21st century. In this scene, the Casa-Grande exhibition will be read by this subject “who speaks to you” as a place (in/of) “traces,” where my accounts, those of former slaves, and those of Black authors of radical critical theory come together to testify that other narratives of violence that still interrupt the daily lives of Black people in Brazil are erased in these places. To this end, I propose the “de-archiving” of what remains of the memory performed in life by Black bodies, in order to dismantle the practices of erasure promoted by these secular institutions, which I intuit as “hegemonic counter-narratives of museums.” Thus, based on the thinking of Kilomba (2020), Sharpe (2023), Hartman (2022; 2024), Moten & Harten (2024), among others, I will “cheat” museums with the accounts of Douglass (2021) because I consider his narratives to be ammunition that, when fired, torment the dreams of sleeping slave owners and de-musealize the memories of Black People in Brazil.Keywords: De-archiving and De-musealization; Black Female Bodies; Everyday Racism; Memories of Enslavement; Museology and Museums.